Swelling and pillaring of the layered precursor IPC-1P: tiny details determine everything - Shamzhy, Mariya; Mazur, Michal; Opanasenko, Maksym; Roth, Wieslaw J; Čejka, Jiří (Dalton transactions (Cambridge, England, 2014)
The influence of swelling (i.e. the size of tetraalkylammonium surfactant molecule, the presence of tetrapropylammonium hydroxide (TPAOH), pH) and pillaring (i.e. the ratio between the swollen precursor IPC-1P and tetraethyl orthosilicate) conditions on the structure and textural properties of the resulting materials was studied in detail for IPC-1P, which is the layered precursor of zeolite PCR. The swelling of IPC-1P proceeds efficiently under basic conditions both in mixed C(n)H(2n+1)N(CH3)3Cl/TPAOH systems and in C(n)H(2n+1)N(CH3)3OH (n = 8, 10, 12, 14, 16, 18) solutions at pH = 13-14. The intercalation of C(n)H(2n+1)N(+)(CH3)3 in IPC-1P resulted in the formation of expanded materials with interlayer distances growing with increasing length of the alkyl chain in C(n)H(2n+1)N(CH3)3(+): 1.59-1.86 (n = 8) < 1.89-2.11 (10) < 2.05-2.26 (12) = 2.08-2.26 (14) < 2.37-2.43 (16) < 2.57-2.71 (18) Å. IPC-2 zeolite was formed during calcination of IPC-1P samples swollen in C(n)H(2n+1)N(CH3)3OH solution, while PCR zeolite can be obtained by calcination of IPC-1P treated with either C(n)H(2n+1)N(CH3)3Cl/TPAOH or C(n)H(2n+1)N(CH3)3Cl. The pillaring of IPC-1P samples swollen with C(n)H(2n+1)N(CH3)3OH provided mesoporous materials with narrow pore size distribution in the range 2.5-3.5 nm. Pillared materials derived from the samples swollen in the presence of TPAOH were characterized by a broader pore size distribution. The optimal TEOS/IPC-1PSW ratio being sufficient for the formation of well-ordered pillared derivatives characterized by improved textural properties (S(BET) = 878 m(2) g(-1), V(total) = 0.599 cm(3) g(-1)) was found to be 1 : 1.5.